DAYA HAMBAT PROBIOTIK DALAM MINUMAN YOGHURT SQUEEZE PLAIN TERHADAP PERTUMBUHAN BAKTERI FUSOBACTERIUM NUCLEATUM - Andriani, Ika; Fitria, Salza Sa’datul Putri (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2024)
Introduction: Periodontal disease is an inflammatory condition that affects the supporting tissues of teeth due to the accumulation of plaque bacteria. Various efforts have been made to control plaque in periodontal disease, one of which is the use of processed products containing probiotics, namely yoghurt. Aim: This study aims to determine the potential probiotic content in one of commercially available plain yoghurt to inhibit the growth of Fusobacterium nucleatum bacteria. Methods: This was a laboratory experimental study employing a disc diffusion method with a post-test-only control group design, comprising three groups with nine replicates each. A bacterial suspension of Fusobacterium nucleatum, standardized to a 0.5 McFarland turbidity, was inoculated onto Mueller-Hinton agar (MHA) plates. Paper discs impregnated with commercially available plain yogurt (treatment group), chlorhexidine (positive control group), and sterile distilled water (negative control group) were then placed on the inoculated MHA. Result: The mean inhibition zone diameter against Fusobacterium nucleatum in the treatment group was 10.8 mm.The Kruskal-Wallis test revealed a statistically significant difference in inhibition zone diameters among the groups (p < 0.001). Conclusion: These findings suggest that the commercially available plain yogurt may possess the potential to inhibit the growth of Fusobacterium nucleatum